(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2023)
The work analyzes the challenges found in the everyday routine of the so-called Project Playing is the Best Medicine for the development of the interdisciplinary work with children undergoing cancer treatment. It is a Collaborative Research-Action, held in 2019, at an institution that assists this target audience in the city of Vitória/ES. The subjects were 4- to 16-year-old children with cancer, their relatives and the different areas of knowledge present in the institution. Before the divergences found with regard to the conception of childhood and games/playful activities, it can thus conclude that the dialogic work, in which there is a consensus from both parts, was fundamental in order to value the children subject and their right to play, through agencies, prominence and cultural productions, this way, overcoming only the functional view, which focus is the treatment compliance.